2005
DOI: 10.1055/s-2005-871955
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine as Efficient Co-Catalyst for Facile Oxidation of Alcohols with Hypervalent(III) Iodine

Abstract: A simple and mild procedure for the facile oxidation of alcohols to ketones and acids using a catalytic quantity of molecular iodine in combination with (diacetoxyiodo)benzene in acetonitrile is described. Direct oxidative methyl esterification of alcohols is also reported in methanol as solvent. Oxidation of alcohols is induced by iodonium ion generated in situ by the chemical oxidation of molecular iodine with (diacetoxyiodo)benzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 5 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…The direct formation of methyl esters from the oxidation of primary alcohols in methanol is well known [20][21][22][23][24]. However, these methods all employ stoichiometric oxidants such as iodine [20], trichloroisocyanuric acid [21], (diacetoxy)iodobenzene [22] or hypochlorite reagents [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct formation of methyl esters from the oxidation of primary alcohols in methanol is well known [20][21][22][23][24]. However, these methods all employ stoichiometric oxidants such as iodine [20], trichloroisocyanuric acid [21], (diacetoxy)iodobenzene [22] or hypochlorite reagents [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods all employ stoichiometric oxidants such as iodine [20], trichloroisocyanuric acid [21], (diacetoxy)iodobenzene [22] or hypochlorite reagents [23,24]. The use of air as the oxidant in this transformation is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have revealed that DIB combined with a catalytic quantity of molecular iodine can oxidize alcohols to ketones, acids and esters under mild reaction conditions. 19 In continuation of this work, we wish to report herein the use of DIB combined with molecular iodine in the facile and direct oxidative methyl esterification of aldehydes (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…For examples, previously reported iodine induced oxidative methods had been invariably carried out in the presence of activating substances such as 2,2,6,6,-tetramethyl-1-piperdinyloxyl (TEMPO), 8 potassium iodide, 9 or (diacetoxyiodo)benzene. 10 To the best of our knowledge, successful utilization of molecular iodine in the absence of any additional promoters in the oxidation of benzylic alcohols to the corresponding carbonyl compounds has been unprecedented.…”
mentioning
confidence: 99%